Supervision interactions and student learning: how supervision can influence learning. (1st February 2021) - Schmutz, Anna; Meyer, Ilse; Archer, Elize
ABSTRACT: Background/Introduction : Supervision interactions are a central part of clinical education. The researcher explored and described the intricate construction of supervision interactions to better understand the influence thereof on student learning. Objectives : The aim of this study was to explore how Clinical Educators and physiotherapy students use supervision interactions toward student learning during clinical education. The perceptions and experiences of Clinical Educators and physiotherapy students were explored and described. Methodology : This study followed a qualitative research approach. The data were obtained by the researcher through semi-structured individual interviews with six students and four Clinical Educators. Themes were identified through thematic analysis. Results : Three themes that contributed to the construction of supervision interactions were developed as contextual, personal and relational elements. The consideration of these elements in supervision interactions influenced student learning and future relationships with patients. Conclusion : The emotionally attuned, effective leadership and management by Clinical Educators are fundamental in the construction of supervision interactions. Contextual, relational and personal elements should be considered in the construction of supervision interactions. Faculty should provide appropriate support to Clinical Educators, students and placements.